Analisis Sistem Pengelolaan Keuangan Produk Pembiayaan Syariah Dengan Akad Murabahah - Wahid Wachyu Adi Winarto; Fatimatul Falah (JPS (Jurnal Perbankan Syariah), 2020)
Cooperatives for Savings and Loans and Sharia Financing are microfinance institutions that collect funds from the public and distribute them to people who need these funds. The purpose of this study was to determine the financial management system of sharia financing with the murabahah contract in the Baitut Tamwil Tazakka Islamic Savings and Loan Cooperative. This research is qualitative research using interview and documentation methods and obtained primary and secondary data results. The results of this study are that the murabahah contract is one of the most dominant contracts in the Baitut Tamwil Tazakka Sharia Savings and Loan Cooperative. Among the products are funding and financing products. In non-performing financing or bad credit, it is known from Non-Performing Financing 0.4%, so to avoid this, the Saving and Loan and Sharia Financing Cooperatives use the 5C principles, namely Character, Capacity, Capital, Collateral, and Condition.